Application of Think Pair Share Type Cooperative Learning Model to Increase Motivation and Mathematics Learning Outcomes Multiplication and Division of Integer Operations for Class VI Students of SDN Sombek - Sukri, Sukri; Supriadi, Akhmad; Rahmaniah, Rima (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Mathematics learning achievement in elementary school (SD) tends to be lower than other subjects. This is because in mathematics learning activities teachers still use teacher-based learning and there is no innovation in mathematics learning. The choice of a teacher-centered learning model is one of the causes of the low motivation and achievement of students' mathematics learning. This study aims to determine the effectiveness of the application of the TPS (Think Pair Share) Cooperative Learning Model on Increasing Motivation and Mathematics Learning Outcomes for Class VI SDN Sombek with a total of 24 students. This research is a classroom action research (CAR). The instruments used in this research are motivation questionnaires and test sheets. Questionnaires were used to collect motivational data and test sheets were used to collect learning outcomes. The data analysis technique uses quantitative and qualitative data analysis techniques. The results showed that students' motivation and learning outcomes in mathematics subjects increased after learning using the Think Pair Share type of cooperative learning model.